Re: Multifaceted impact of caffeic acid phenethyl ester (CAPE) in experimental myocardial injuries - İlhan, Selçuk (Turkish Society of Cardiology, 2015)
[Abstract Not Available]
Keywords: caffeic acid phenethyl ester; isoprenaline; animal experiment; animal model; animal tissue; heart muscle injury; hypertension; Letter; nonhuman; rat